PERSONAL HYGIENE KARYAWAN DI PONDOK BAKSO MAS TRIS PADANG - Putra, Ilham Adiaf (journal of residu, 2019)
Personal Hygiene is an action to maintain one's hygiene and health for physical and psychological well-being. However, in reality the personal Hygiene of employees is not considered. One solution to overcome this problem is the application of personal hygiene in Pondok Bakso Mas Tris. The purpose of this study was to find out personal hygiene, general health, exercise and fresh air, cleanliness of employees and cleanliness of clothes. Data collection techniques by means of observation, interviews and documentation. Based on the overall questionnaire results obtained statements from consumers as follows: strongly agree as much as 62.96%, agree 34.81% and less agree 2.22%, disagree 0%. So that it can be concluded that public health (general health) pay more attention to employees in maintaining general health in serving consumers. Based on the overall questionnaire results obtained statements from consumers as follows: strongly agree as much as 69.16%, agree 17.22% and disagree 8.47%, disagree 5.13%. So that it can be concluded that personal hygiene (personal cleanlines) on mas tris meatball huts pay little attention to personal hygiene and underestimate personal hygiene that has an impact on service to consumers who come. Based on the results of the consumer kepuasana questionnaire on mas tris meatball hut, it was found that strongly agreed 63.11%, agreed 35.11% did not agree 1.78% did not agree 0.0%. looks clean and neat when working. So that consumers love visiting continue to take care of the mas tris meatball hut. So it can be concluded that the Personal Hygiene at Pondok Bakso Mas Tris on Public Health, Personal Hygiene and Work Wear is very much considered.